2014
DOI: 10.1089/neu.2014.3422
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions and Theory of Mind as Predictors of Social Adjustment in Childhood Traumatic Brain Injury

Abstract: This study examined whether executive function and theory of mind mediate the effects of pediatric traumatic brain injury (TBI) on social adjustment, relative to children with orthopedic injury (OI). Participants included 19 children with severe TBI, 41 children with complicated mild/moderate TBI, and 57 children with OI. They completed measures of executive function, as well as cognitive, affective, and conative theory of mind. Parents provided ratings of children's social adjustment. Children with severe TBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 40 publications
5
40
1
1
Order By: Relevance
“…Studies of children with neurological disorders or acquired brain injury are also informative. For instance, children with traumatic brain injury (TBI) show both broad ToM and EF deficits (Robinson et al, 2014). Moreover, Dennis et al (2013) examined how injury to specific brain networks was associated with different aspects of ToM.…”
Section: Neurological Disorders As Clues To the Tom-ef Associationmentioning
confidence: 99%
“…Studies of children with neurological disorders or acquired brain injury are also informative. For instance, children with traumatic brain injury (TBI) show both broad ToM and EF deficits (Robinson et al, 2014). Moreover, Dennis et al (2013) examined how injury to specific brain networks was associated with different aspects of ToM.…”
Section: Neurological Disorders As Clues To the Tom-ef Associationmentioning
confidence: 99%
“…These analyses have identified mediation effects of verbal working memory on math performance, 50 of selfregulation skills on social and behavioral functioning, 51 and of theory of mind skills on social outcomes. 52 To our knowledge, no prior study has examined neuropsychological skills as mediators of the effect of childhood TBI on long-term adaptive functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Children with moderate TBI have been found to have working memory deficits at least one year post-injury, 10 and children with mild–moderate TBI have been found to have theory of mind impairments one–five years post-injury. 11 Attention can also be affected; in one study, at one year post-injury, parents reported new moderate to severe attention difficulties for 5% of children with mild TBI and 15% of children with moderate TBI. 12 Children with TBI also have been observed to have lasting difficulties with response inhibition and inhibitory control.…”
Section: Introductionmentioning
confidence: 99%